ريادة الاعمال في ظل جائحة كورونا و تأثيرها في مواقف وتصورات عينة من سكان مدينة سوق أهراس - نور الهدى دريدي; ريان عشايشية (My University, 2022)
The Corona pandemic has caused unprecedented effects on society and the economy, as well as many challenges for entrepreneurs and owners of business projects, and it has affected the attitudes and perceptions of individuals regarding their intentions and plans. to establish new projects or expand existing ones. Analyze and understand the most important effects and challenges resulting from the closure and quarantine over the past two years on entrepreneurship, and this research concluded after analyzing the trends of a sample of 45 people residing in the city of Souk Ahras that there is a significant and statistically significant effect of the effects of the Corona pandemic on the attitudes and perceptions of individuals.Research has proven the existence of a state of great uncertainty and uncertainty for individuals about the future of entrepreneurship ............................................ أحدثت جائحة كورونا تأثيرات غير مسبوقة على المجتمع و الاقتصاد كما تسببت في العديد من التحديات لرواد الأعمال و أصحاب المشاريع التجارية و هدا ما اثر على مواقف و تصورات الأفراد بخصوص نواياهم و مخططاتهم لإنشاء مشاريع جديدة أو التوسع في المشاريع الحالية على هدا الأساس يهدف هدا البحث إلى تحليل و فهم اهم الأثار و التحديات الناتجة عن الإغلاق و الحجر الصحي في السنتين الماضيتين على ريادة الأعمال و خلص هدا البحث بعد تحليل اتجاهات عينة من 45 فرد القاطنين بمدينة سوق أهراس إلى وجود تأثير كبير و دال إحصائيا لآثار جائحة كورونا على مواقف و تصورات الأفراد كما أن البحث اثبت وجود حالة شك و عدم يقين كبيرة للأفراد بشان مستقبل ريادة الأعمال